Будівлі османського Хаджибея (Одеси) 1760 – 1780-х рр.: за матеріалами опублікованих джерел та вітчизняної історіографії - Гончарук, Т. (Чорноморська минувшина, 2015)
Стаття присвячена висвітленню в опублікованих джерелах та історіографії ХІХ – початку ХХІ ст. будівель оcманського Хаджибея (Одеси) другої половини ХVIII ст. Зокрема, подано інформацію про можливе розташування та розміри Хаджибейської фортеці. Узагальнено інформацію про споруди портової інфраструктури Хаджибея (маяк, пристань та ін.), казенні та приватні будівлі. Розглянуто долю окремих споруд під час російсько- турецьких війн 1768 - 1774 рр. та 1787 - 1791 рр., й під російської владою в кінці XVIII - першій половині ХІХ ст. The information about buildings of Ottoman Khadzhybei in XVIII-th century is examined in the article. To found out this intelligence author used the miscellaries of sources which were published princilally in XIX - the beginning of XX-th centuries and also the brief from Ukrainian historiography in the XIX-th - the beginning of XXIth centuries. The works of H. Kastelno, A. Skalkovskyi, V. Yakovlev, M. Murzakevych, K. Smolianinov, S. Borovyi, O. Sereda, A. Krasnozhon and other scientists were involved for research. The main attention among the construction of Ottoman Khadzhybei is paid to the fortress including the problems of its location and sizes. The materials about Khadzhybei lighthouse and wharf were also studied. It was noticed that the both of these two structures left in town even after the camming of Khadzhybei into the passesion of Russian Empire. The disposal of wells, the Pasha's house, the Mosque, the bakery and others of official buildings also was ascertained in exploration. The fate of particular constraction in Khadzhybei during the Russo-Turkish wars of 1768-1774 and of 1787-1791 was traced. The information about private architectures in Khadzhybei on example of the Simon Asporidi' Coffeehouse which was situated in Odesa till the first quarter of XIХ-th century was given apart in this adumbration. It was found out that the last construction of Ottoman Khadzhybei which was saved in Odesa was the turkish bath-house ruined in 1840. Статья рассматривает освещению в опубликованных источниках и историографии ХІХ - начала ХХІ в. строений османского Хаджибея (Одессы) второй половины ХVIII в. В частности, подана информация о возможном расположении и размерах Хаджибейской крепости. Также обобщена информация о сооружениях портовой инфраструктуры Хаджибея (маяк, пристань и др.), казенных и частных зданиях. Рассмотрена судьба отдельных сооружений во время русско-турецких войн 1768 - 1774 гг. и 1787 - 1791 гг. и под российской властью в конце XVIII - первой половине ХІХ в.